Safeguarding the Garífuna: Initiatives and Challenges in Language Preservationon the Caribbean Coast of Guatemala - Fiedler, Lukas (Íkala, Revista de Lenguaje y Cultura, 2025)
This article aims to analyze the current situation of linguistic contact between Spanish and Garifuna in the community of Livingston (Guatemala), with the purpose of understanding the factors that influence the displacement or mainte-nance of Garifuna and evaluating the effectiveness of educational and community strategies aimed at its preservation. The data were obtained through a sociolinguistic question-naire and semi-structured interviews conducted during fieldwork between 2024 and 2025. The analysis focuses on the role of the home, community initiatives, and intercultural bilingual education in language transmission. The results show that, although Garifuna continues to be spoken in Livingston, the younger generation no longer acquires it as their mother tongue, and Spanish predominates in everyday life. Among the most influential factors are monolingual schooling, lack of family transmission, and the limited effectiveness of language policies. It is concluded that the revitalization of Garifuna requires effective coordination between schools, families, and communities, better teacher training, and sustainable strategies that integrate Garifuna as an active component of cultural identity and daily communication.